Completely resected stage III melanoma controversy - Perić, Barbara (Radiology and oncology (Ljubljana), 2021)
Background Two prospective randomized studies analysing cutaneous melanoma (CM) patients with sentinel lymph node (SLN) metastases and rapid development of systemic adjuvant therapy have changed our approach to stage III CM treatment. The aim of this study was to compare results of retrospective survival analysis of stage III CM patients% treatment from Slovenian national CM register to leading international clinical guidelines. Patients and methods Since 2000, all Slovenian CM patients with primary tumour % TIb are treated at the Institute of Oncology Ljubljana and data are prospectively collected into a national CM registry. A retrospective analysis of 2426 sentinel lymph node (SLN) biopsies and 789 lymphadenectomies performed until 2015 was conducted using Kaplan-Meier survival curves and log-rank tests. Results Positive SLN was found in 519/2426 (21.4%) of patients and completion dissection (CLND) was performed in 455 patients. The 5-year overall survival (OS) of CLND group was 58% vs. 47% of metachronous metastases group (MLNM) (p = 0.003). The 5-year OS of patients with lymph node (LN) metastases and unknown primary site (UPM) was 45% vs. 21% of patients with synchronous LN metastasis. Patients with SLN tumour burden 1.0 mm was similar to the MLNM group (49% vs. 47%; p = 0.280). Conclusions Stage III melanoma patients is a heterogeneous group with significant OS differences. CLND after positive SLNB might still remain a method of treatment for selected patients with stage III.
Keywords: biopsija varovalne bezgavke; cutaneous melanoma; kirurško zdravljenje; kožni melanom; sentinel node biopsy; surgery treatment